Claudin-5 Affects Endothelial Autophagy in Response to Early Hypoxia - Yu, Ping; Li, Yanyu; Zhong, Gaoliang; Li, Wen; Chen, Bing; Zhang, Jingjing (Frontiers in Physiology, 2021)
Hypoxic injury to cerebrovascular endothelial cells after stroke leads to blood-brain barrier (BBB) dysfunction, which is commonly associated with disruptions of endothelial tight junctions and increased permeability. Therefore, maintaining the structural integrity and proper function of the BBB is essential for the homeostasis and physiological function of the central nervous system (CNS). Our previous study revealed that autophagy functions on protecting the BBB by regulating the dynamics of Claudin-5, the essential tight junction protein, under short-term starvation or hypoxia conditions. Here, we show that in zebrafish and in vitro cells, loss of membranous Claudin-5 conversely determine the occurrence of hypoxia-induced autophagy in cerebrovascular endothelial cells. Absence of endothelial Claudin-5 could partly attenuate endothelial cell apoptosis caused by short-term hypoxic injury. Mechanism studies revealed that under hypoxic conditions, the existence of membranous Claudin-5 affects the stimulation of hypoxia inducible factor 1 subunit alpha (HIF-1a) and the induction of nitric oxide synthase (iNOS), which are responsible for the translocation of and endocytosis of caveole-packaged Claudin-5 into cytosol. Meanwhile, loss of Claudin-5 affects the generation of reactive oxygen species (ROS) and the downstream expression of BNIP3. These together suppress the endothelial autophagy under hypoxia. This finding provides a theoretical basis for clarifying the mechanism of hypoxia-induced BBB injury and its potential protection mechanisms.